Assessment of menopausal symptoms using modified menopause rating scale among urban women doctors of India - Patankar, Ujjwala S.; Sonak, Mangala M.; Patankar, Sameer U.; Patil, Rashmi R.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The study was conducted to assess the commonly reported menopausal symptoms among urban women doctors using modified menopause rating scale (MRS). Methods: The study was carried out in the society by google link. Convenient sample of 100 women doctors were included in the study. Menopausal symptoms were assessed using modified MRS. Results: In present study, 3 (3%) female doctors had premature menopause, 5 had menopause at 40-44 years, 15 (15%) had menopause at 45-49 years, 77 (77%) had menopause while no patient had menopause after 55 years. Hot flushes were seen in 70 (79%) women, heart discomfort/ palpitation was seen in 2 (2%) women, muscle and joint problems were seen in 30 (30%) women, sleeping problems were seen in 20 (20%) women. Depressive mood was seen in 2 (2%) women, irritability was seen in 12 (12%) women, an anxiety was seen in 22 (22%) women while physical and mental exhaustion was seen in 34 (34%%) women. Sexual problems were seen in 32 (32%) women, bladder problems were seen in 8 (8%) women dryness of the vagina was seen in 35 (35%) women (Table 6). Conclusions: Hot flushes and joint problems were the most common followed by urogenital symptom, sleep disturbance, and anxiety in the study. Menopausal symptoms were less prevalent. Busy schedule, self-confidence due to independent nature and constructive work might be the reason.